2008
DOI: 10.1002/fld.1895
|View full text |Cite
|
Sign up to set email alerts
|

Jet impingement onto a tapered hole: Influence of jet velocity and hole wall velocities on heat transfer and skin friction

Abstract: SUMMARYJet impingement onto a hole with elevated wall temperature can be associated with the high-temperature thermal drilling, where the gas jet is used for shielding the hole wall from the high-temperature oxidation reactions as observed in the case of laser drilling. In laser processing, the molten flow from the hole wall occurs; and in the model study, the hole wall velocity resembling the molten flow should be accounted for. In the present study, gas jet impingement onto tapered hole with elevated tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They indicated that the changes in the structure of striations over the thickness of the sheet being cut were closely related to aerodynamic features of the jet flows in the laser produced kerf. Jet impingement studies in relation to laser processing were carried out by Yilbas et al (2002Yilbas et al ( , 2003 and Shuja et al (2009). However, the flow situation is considered to be two dimensional and axisymmetric, which was the case for the laser drilling applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that the changes in the structure of striations over the thickness of the sheet being cut were closely related to aerodynamic features of the jet flows in the laser produced kerf. Jet impingement studies in relation to laser processing were carried out by Yilbas et al (2002Yilbas et al ( , 2003 and Shuja et al (2009). However, the flow situation is considered to be two dimensional and axisymmetric, which was the case for the laser drilling applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, jet impingement onto a heated slot (kerf) in relation to laser cutting process is carried out. The flow field in the kerf is simulated using the practical assisting gas parameters (Shuja et al, 2009). The heat transfer rates form the kerf surface and the skin friction at the kerf wall are predicted.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that the deterioration of cut quality with the gas pressure and stand-off distance was closely related to the mass flow rate reduction in the cut section. Shuja et al (2009) and Yilbas et al (2003) investigated heat transfer from the circular hole due to jet impingement. Their findings revealed that the wall temperature of the hole influenced the mass flow rate through the hole and the Nusselt number.…”
mentioning
confidence: 99%